The Impact of Demographics on Productivity and Inflation in Japan - Westelius, Niklas (IMF Working Papers; Working Paper ;, 2016)
Is Japan's aging and, more recently, declining population hampering growth and reflation efforts? Exploiting demographic and economic variation in prefectural data between 1990 and 2007, we find that aging of the working age population has had a significant negative impact on total factor productivity. Moreover, prefectures that aged at a faster pace experienced lower overall inflation, while prefectures with higher population growth experienced higher inflation. The results give strong support to the notion that demographic headwinds can have a non-trivial impact on total factor productivity and deflationary pressures.